2022
DOI: 10.3390/nutraceuticals2020004
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Extraction of Pittosporum angustifolium Lodd. Used in Traditional Aboriginal Medicine: A Mini Review

Abstract: Numerous native Australian plants are widely used as traditional medicines by the Australian Aboriginal and Torres Strait Islander peoples. Among the native plants, Pittosporum angustifolium Lodd. (Gumby Gumby) is claimed to be a promising medicinal plant in the treatment of a wide range of diseases that includes viral symptoms (colds and coughs), eczema, cancer, muscle aches, varicose veins, and many more. Various extraction techniques are used to extract the bioactive compounds of P. angustifolium, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These compounds are known for their strong antioxidant, anticancer, anti-inflammatory, and antifungal properties [ 16 ]. Previous studies have also identified chlorogenic acid in P. angustifolium leaves [ 17 , 18 , 19 ]. Additionally, our previous work has suggested the presence of chlorogenic acid in crude MeOH extracts of P. angustifolium leaves [ 14 , 20 ].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These compounds are known for their strong antioxidant, anticancer, anti-inflammatory, and antifungal properties [ 16 ]. Previous studies have also identified chlorogenic acid in P. angustifolium leaves [ 17 , 18 , 19 ]. Additionally, our previous work has suggested the presence of chlorogenic acid in crude MeOH extracts of P. angustifolium leaves [ 14 , 20 ].…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, the subfractions could contain fewer isolated compounds, which may explain the low or no cytotoxicity observed. Although numerous studies have identified triterpenoid saponins, terpenoids, phenols, and coumarin compounds isolated from P. angustifolium as having potential anticancer properties [10,17,18,35,36], only a few have been shown to be effective in vitro. Backer et al (2016) screened ten acylated saponins for their ability to inhibit human DNAtopoisomerase I, an enzyme responsible for resolving torsional stress associated with DNA replication, transcription, and chromatin condensation [37].…”
Section: Cytotoxic Activity and Hplc Profilingmentioning
confidence: 99%
See 1 more Smart Citation